Strategy for Reducing Employee Turnover Intention: The Influence of Organizational Culture and Work Environment as Mediated by Job Satisfaction - Syarif, Diah Syartika; Soelistya, Djoko; Suyoto, Suyoto (MANAZHIM, 2024)
The research aims to analyze the influence of Organizational culture variables and Work environment variables on turnover intention variables, to analyze the influence of Organizational culture variables and Work environment variables on Job satisfaction variables and to analyze the influence of Organizational culture and Work environment on turnover intention with Job satisfaction as a mediating variable in PT Adhi Karya Manyar Smelter Gresik Project, The type of research used in this research is quantitative research. The population and sample in this study were employees of PT Adhi Karya Manyar Smelter Gresik Project, totaling 271 respondents. The research results show that Organizational culture and Work environment have a positive and significant influence on Turnover intention. Organizational culture has a positive and significant influence on job satisfaction, while work environment does not have a significant influence on job satisfaction. Job satisfaction has a positive and significant influence on turnover intention. Organizational culture has a significant influence on turnover intention through job satisfaction as mediation, but work environment does not have a significant influence on turnover intention through job satisfaction as mediation. From the research results of PT Adhi Karya Manyar Smelter Gresik Project, it is recommended to condition the organizational culture that is implemented, and provide or complete work facilities so that employees feel more at home at work, apart from that, increasing salaries or giving bonuses can also be done for employees to prevent turnover intention from increasing.